The prebiotic potential of alternansucrase-based glucooligosaccharides: the effects on short-chain fatty acids production and microbiome diversity - Ozulku, Gorkem; Harris, Hannah C.; Savva, George M.; Ahn-Jarvis, Jennifer H.; Ispirli, Humeyra; Dertli, Enes; Warren, Frederick J. (ELSEVIER, 2025)
Glucooligosaccharides (GLOS) produced by glucansucrases via acceptor reactions are oligosaccharides that transit upper intestinal tract and evade digestion and may be considered to be a prebiotic. The prebiotic function of GLOS can be dictated by the type of acceptor sugar used during its production. Therefore, the prebiotic effect on the gut microbiome and short chain fatty acids (SCFAs) production can be used to inform the selection of acceptor sugars. In this study, alternansucrase-based GLOS derived from different acceptor sugars (melibiose, cellobiose and lactose) and inulin (positive control) were investigated using in vitro colon model fermentation to examine their prebiotic effect and SCFAs production. Microbiome composition was determined using shotgun metagenomics. SCFAs and lactate formation was determined using 1H NMR spectroscopy. Fusicatenibacter saccharivorans and Bacteroides uniformis appeared to increase in abundance after 24 h following fermentation of all three GLOS. The highest abundance for Bifidobacterium longum was seen after supplementation with lactose derived GLOS. Fermentation of GLOS appeared to produce around twice as much acetate than fermentation with inulin, while similar amounts of other SCFAs and lactate were produced. Melibiose derived GLOS supplementation in healthy 3 donors increased F. saccharivorans while inulin supplementation promoted Lactobacillales in order level. This study suggests that there may be beneficial effects of GLOS's on gut microbiome composition and metabolite composition, relative to the effects seen for inulin.
Keywords: Glucansucrases; Acceptor reactions; Short chain fatty acids; Gut microbiome; GUT MICROBIOTA; GLUCANSUCRASE; OLIGOSACCHARIDES; DEXTRANSUCRASE; LACTOBACILLUS; PROPIONATE; BUTYRATE; Food Science & Technology